Planetary Normal Mode Computation: Parallel Algorithms, Performance, and Reproducibility - Shi, Jia; Li, Ruipeng; Xi, Yuanzhe; Saad, Yousef; de Hoop, Maarten V. (IEEE transactions on parallel and distributed systems, 2021)
This article is an extension of work entitled "Computing planetary interior normal modes with a highly parallel polynomial filtering eigensolver." by Shi et al. , [1] originally presented at the SC18 conference. A highly parallel polynomial filtered eigensolver was developed and exploited to calculate the planetary normal modes. The proposed method is ideally suited for computing interior eigenpairs for large-scale eigenvalue problems as it greatly enhances memory and computational efficiency. In this article, the second-order finite element method is used to further improve the accuracy as only the first-order finite element method was deployed in the previous work. The parallel algorithm, its parallel performance up to 20k processors, and the great computational accuracy are illustrated. The reproducibility of the previous work was successfully performed on the Student Cluster Competition at the SC19 conference by several participant teams using a completely different Mars-model dataset on different clusters. Both weak and strong scaling performances of the reproducibility by the participant teams were impressive and encouraging. The analysis and reflection of their results are demonstrated and future direction is discussed.